Efektifitas Strategi Koersif Perda Kabupaten Sleman Nomor 12 Tahun 2020 Terkait Tertib Sosial Penanganan Pengemis Jalanan - Heni Ristiawan (CV. ULIL ALBAB CORP, 2022)
This article explores and analyzes coercive strategies in dealing with street beggars who are not in accordance with the values ​​prevailing in society (the living law). A beggar is a person who practices begging in public and in various ways to attract the feelings of compassion and compassion of others. The emergence of the phenomenon of street beggars in Sleman Regency is one of the implications of this problem. Sleman Regency is a city that is trying to deal with the problem of street beggars. The handling of street beggars is contained in the Regulation of the Head of the Sleman Regency Number 12 of 2020. In the regulation there is a coercive strategy that has an article on punishment for street beggars. The purpose of this study was to determine the factors that make Sleman Regency the allure of street beggars and how effective the coercive strategy is in dealing with street beggars. To find out about this, of course, this journal tries to see the extent of the implementation of the Perda.